2018
DOI: 10.1002/smll.201801154
|View full text |Cite
|
Sign up to set email alerts
|

SnO2: A Wonderful Electron Transport Layer for Perovskite Solar Cells

Abstract: The highest power conversion efficiency of perovskite solar cells is beyond 22%. Charge transport layers are found to be critical for device performance and stability. A traditional electron transport layer (ETL), such as TiO , is not very efficient for charge extraction at the interface, especially in planar structure. In addition, the devices using TiO suffer from serious degradation under ultraviolet illumination. SnO owns a better band alignment with the perovskite absorption layer and high electron mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
524
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 731 publications
(532 citation statements)
references
References 83 publications
6
524
0
2
Order By: Relevance
“…[21][22][23] Taking this into account, electron beam evaporated NiO x as an HTL is improving the device robustness against temperature stress, which is usually the only stress factor that is not limited during outdoor operation but a common problem for devices employing organic HTLs like spiro-MeOTAD or PTAA. [22,74,75,78] Thus, the use of alternative front side oxides next to TiO x and SnO x absorbing the UV radiation without changing the chemical properties of the layer might be of key importance to overcome this limiting factor. [22,[72][73][74][75] It was shwon before that UV radiation degrades perovskite solar cells at the front side interface of the metal oxide charge transport material and the perovskite absorber layer.…”
Section: Robustness Of Nickel Oxide-based Solar Cells Under Externalmentioning
confidence: 99%
“…[21][22][23] Taking this into account, electron beam evaporated NiO x as an HTL is improving the device robustness against temperature stress, which is usually the only stress factor that is not limited during outdoor operation but a common problem for devices employing organic HTLs like spiro-MeOTAD or PTAA. [22,74,75,78] Thus, the use of alternative front side oxides next to TiO x and SnO x absorbing the UV radiation without changing the chemical properties of the layer might be of key importance to overcome this limiting factor. [22,[72][73][74][75] It was shwon before that UV radiation degrades perovskite solar cells at the front side interface of the metal oxide charge transport material and the perovskite absorber layer.…”
Section: Robustness Of Nickel Oxide-based Solar Cells Under Externalmentioning
confidence: 99%
“…Recently, it was reported that adding cesium (Cs) at the cation site can significantly reduce fabrication temperature for perovskite films . Due to the abundance of the precursor components and ease of fabrication, a variety of low‐temperature techniques has been developed to promote the performance of the PSCs in the past few years.…”
Section: Perovskite Absorber Layersmentioning
confidence: 99%
“…[37] You et al have successfully used high crystallinity of SnO 2 nanoparticles as the ETL for PSCs in 2016. [37] You et al have successfully used high crystallinity of SnO 2 nanoparticles as the ETL for PSCs in 2016.…”
Section: Snomentioning
confidence: 99%
“…[19] In 2018, by the rational design of the surface passivation layer of perovskite, a certificated efficiency as high as 23.32% was reported. [37] To solve this problem, Phenyl-C61-butyric acid methyl ester (PCBM) was applied to passivate both the SnO 2 /perovskite interface and perovskite grain boundaries by Yan et al, leading to a PCE of 19.12% with Voc of 1.12 V, Jsc of 22.61 mA •cm -2 , and FF of 75.8% (Figure 6e). For example, Liu et al added ethylenediaminetetraacetic acid (EDTA) into SnO 2 (E-SnO 2 ) to increase electron mobility of the ETL, which is increased by about 3 times compared with the control devices.…”
Section: Snomentioning
confidence: 99%